Hume e o problema da identidade pessoal - Santos, Susie Kovalczyk dos (2017)
This dissertation investigates the personal identity problem on David Hume’s writings on Treatise of Human Nature. For this aim, I present the Humean conception of self concerning the operations of the understanding and of the passions or emotions, as well as two interpretative controversies arising from it. Once Hume considers the notion of substance unintelligible, and denies that there is an impression that is one and the same throughout one’s life, he considers imperfect, in section Of personal identity, the attribution of identity and simplicity to the self. All we have access about the mind are the sucessive experiences or perceptions, related through associative qualities which leads us to tend to believe in the unity of the self. If there is something beyond the sucessive perceptions which unites them, it cannot be discovered through experience. The first interpretative controversy in question concerns if, from one side, much of what Hume proposes in Book I is reaffirmed by him in the Appendix, from the other side, he claims there is one aspect that his theory was not successful in explaining. However, when he sets the problem, for which he admits he does not find a viable solution, the principles that he claims he cannot either reconcile or reject are not incompatibles with each other and also they are relevant to other issues addressed in the Treatise, not restricting their impact to the problem of personal identity. What, then, is the problem that Hume identifies in his theory of personal identity in Book I? Hume reintroduces the notion of self throughout Book II, this time as an object of pride, stating at times that we not only have an idea of self, but also an impression. The second controversy, therefore, concerns whether there are different notions of self in the Treatise, one presupposed by pride and another produced by it, or if Hume develops different aspects of the same conception of self, so that the self as a bundle of perceptions is the same implied by sympathy and produced, as an object, by pride. This dissertation unrolls and argues these problems, seeking to present how Hume's writings in books I and II on the notion of self complement each other and to what extent the human natural propensity to attribute simplicity and identity to the self is due not only to the similarity, causality and memory, as defended in Book I, but also due to the passions.